'Casar bem' : estratégias matrimoniais e econômicas na região de colonização italiana do Rio Grande do Sul (1906-1970) - Busato, Marinilse Candida Marina (2017)
The present work analyzes the trajectory of the families of Italian immigrants Pandolfo, Bernardi, Lunardi and their ramifications, with the Busato family as the guiding thread and interconnection link. These Italian immigrants from Veneto urban areas settled in the headquarters of the Guaporé colony at the beginning of the 20th century, where they established a complex commerce network, which included the district of Vila Maria to the Guaporé headquarters, active until the decade of 1970, temporal cut of the research. The research is justified by the important role played by traders, connecting urban and rural areas, and shipping goods through the port of Muçum, 44 km away from Guaporé headquarters. Still, the research on the Guaporé colony, created in 1892, due to the extensive territorial occupation of the "mother colony" of Caxias do Sul, is scarce, and there are few studies on Italian immigration in urban centers, with emphasis on the conditions of Emigration from Italy to Brazil, including the family division on both sides of the ocean. The theoretical and methodological analysis follows in the line of Italian micro-history and the use of oral sources. The reduction of the scale of analysis, the method of indiciaria and the exhaustive exploration of the sources allowed tracing the familiar trajectories of this group of traders, revealing signs of the alliances and strategies used for social, economic and political ascension. From the Busato family, it was rebuilt its commercial network branched through the interior of Guaporé, articulated and consolidated through marriages between families of immigrants and merchants, kept up to the third generation in Brazil. Therefore, the study contributes to the historiography of Italian immigration, when dealing with trajectories of immigrants in urban space, inserted in commercial activity, in a region of later colonization - Guaporé colony -, and to give visibility to the construction of a sewn family network Via marriages, and the rise of an economic, social and political elite that dominated the entire region for nearly a century. The merchants 'children then married merchants' children through an economic strategy aimed at maintaining and expanding the family business, evolving from merchants to industrialists and expanding to other regions not properly founded by Italian colonization, and to interact economically with others Groups of immigrants, and exporting products to other continents. Therefore, our work aims to demonstrate that even the marital exceptions of the large group were seen and thought as strategies, a stepping stone for economic and social growth, demonstrating that unlike the large number of works referring to Italian immigration in Rio Grande do Sul, nor All the Italians contributed miserably and without financial perspective in the southern colonies, and the social prestige was as important as the constitution of this new social elite.